Palynological Investigations of Miocene Deposits on the New Siberian Archipelago (U.S.S.R.) - Zyryanov, Eugene V. (ARCTIC, 1992)
New paleobotanical data (mainly palynological) are reported from Miocene beds of the New Siberian Islands. The palynoflora has a number of distinctive features: the presence of typical hypoarctic forms, the high content taxa representing dark coniferous assemblages and the considerable proportion of small-leaved forms. Floristic comparison with the paleofloras or the Beaufort Formation in arctic Canada allows interpretation of the evolution of the Arctic as a landscape region during Miocene-Pliocene time. The paper is a preliminary analysis of the mechanisms of arctic florogenesis. The model of an "adaptive landscape" is considered in relation to the active eustatic drying of polar shelves.Key words: palynology, U.S.S.R., New Siberian Islands, Miocene, Arctic, florogenesis RÉSUMÉ. On rapporte de nouvelles données paléobotaniques (principalement palynologiques) venant de couches datant du miocène situées dans l’archipel de la Nouvelle-Sibérie. La palynoflore possède un nombre de caractéristiques particulières, parmi lesquelles, la présence de formes hypoarctiques typiques, la grande quantité de taxons représentant des assemblages de conifires sombres, ainsi qu’une collection considérable de formes à petites feuilles. Une comparaison floristique avec les paléoflores de la formation de Beaufort dans l’Arctique canadien permet d’interpréter l’évolution de l’Arctique en tant que zone peuplée d’espèces végetales durant le miocène et le pliocène. Cet article est une analyse préliminaire des mécanismes de la genèse de la flore arctique. Le modèle d’un paysage adaptatif est envisagé en rapport avec l’assèchement eustatique actif des plates-formes polaires.Mots clés: palynologie, U.R.S.S, archipel de la Nouvelle-Sibérie, miocène, Arctique, genèse de la flore